(untitled) (Canadian Journal of Counselling and Psychotherapy, 2020)
Arts-based research (ABR) continues to grow as a dynamic practice that is deeply influenced by critical theory and entwined with social justice aims. This article addresses three important topics at the intersection of ethics and ABR: how researchers and members of research ethics boards articulate and perceive uncertainty within the creative process, who is involved in the research, and how the arts may be incorporated into research in a manner that attends to risks of potential harm and to ways of mitigating these risks. Creative arts therapies will be highlighted regarding skills and training that promote ethical practice in ABR.